The second one, and you as well ☺️
The answer is “A” as when the width is multiplied by the row foot, you get approximately 3 times the amount.
I hope that’s correct and I hope I could help :)
<h2>
Answer:</h2>
<u>- Real and rational number</u>.
<h2>
Step-by-step explanation:</h2>
<em>It's a rational number because it can be represented by the integer of integer numbers. It's also a real number because rational numbers belong to the real set of numbers and the number doesn't contain an imaginary component (i).</em>
<em />
<em>It's not a natural or whole number because it can't be used to count or order things.</em>
<em>It's not an integer because it can't eb written without using a fractional component.</em>
<em />
Make more sense ou of this question and I can help you out more ok?
Answer:
h=6
Step-by-step explanation:
since
is an equation for a line which intersects with the curve
. The point of intersection, let's say
, should satisfy the two equations. As a result, the value of y in the second equation can be replaced with the value of y in the first equation as the following,
![3y^2 = 3(hx-2)^2 = 9x^2 - 6x +1\\3(h^2x^2 -4hx + 4) = 9x^2 - 6x + 1\\3h^2 x^2 -12hx +12 = 9x^2 - 6x +1](https://tex.z-dn.net/?f=3y%5E2%20%3D%203%28hx-2%29%5E2%20%3D%209x%5E2%20-%206x%20%2B1%5C%5C3%28h%5E2x%5E2%20-4hx%20%2B%204%29%20%3D%209x%5E2%20-%206x%20%2B%201%5C%5C3h%5E2%20x%5E2%20-12hx%20%2B12%20%3D%209x%5E2%20-%206x%20%2B1)
therefore, the latter equation can be rewritten in a quadratic equation form as the following,
= 0
if the line is tangent to the curve, it means that the line touches the curve at one point, therefore the discernment of the second order equation will be equal to zero for the famous quadratic equation solution.
![b^2 -4ac =0](https://tex.z-dn.net/?f=b%5E2%20-4ac%20%3D0)
where
and
, as a result, the following equations can be deduced,
![(12h-6)^2 - 4*(9-3h^2)*(-11) = (144h^2 -144h +36) - (36 -12h^2)*(-11)=\\(144-(-12)*(-11)h^2 ) -144h +36 -(36*(-11)) =\\12 h^2 -144h +432 =0](https://tex.z-dn.net/?f=%2812h-6%29%5E2%20-%204%2A%289-3h%5E2%29%2A%28-11%29%20%3D%20%28144h%5E2%20-144h%20%2B36%29%20-%20%2836%20-12h%5E2%29%2A%28-11%29%3D%5C%5C%28144-%28-12%29%2A%28-11%29h%5E2%20%29%20%20-144h%20%2B36%20-%2836%2A%28-11%29%29%20%3D%5C%5C12%20h%5E2%20-144h%20%2B432%20%3D0)
therefore, dividing both sides by 12
![h^2 -12 +36 =0\\(h-6)^2 =0\\h=6](https://tex.z-dn.net/?f=h%5E2%20-12%20%2B36%20%3D0%5C%5C%28h-6%29%5E2%20%3D0%5C%5Ch%3D6)